2019
DOI: 10.33369/j.akuntansi.9.2.111-130
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Karakteristik Pemerintah Daerah Dan Opini Audit Terhadap Kinerja Pemerintah Provinsi Di Indonesia

Abstract: This research aims to attest, examine and analyze the influence of local government characteristics and audit opinions on the performance of provincial governments in Indonesia. The characteristics of the local government are proxied by the size of the regional government, regional prosperity, capital expenditure. The performance of the provincial government uses a score indicator for Local Government Performance Evaluation (EKPPD). The population of this study amounted to 34 provincial governments in Indonesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 0 publications
1
11
0
3
Order By: Relevance
“…Therefore, it can be concluded that Ha3 is accepted, which means that Audit Opinion has an effect towards the Performance of Local Governments. This result is in line with the studies conducted by Andani & Respati (2019); Aswar (2019); Dewata et al (2018); as well as Sutopo and Siddi (2018), which used samples from Districts/Cities in the whole of Indonesia in the period of 2010-2018. The result of the study showed that Audit Opinion has a significant and positive effect.…”
Section: Modelsupporting
confidence: 90%
See 2 more Smart Citations
“…Therefore, it can be concluded that Ha3 is accepted, which means that Audit Opinion has an effect towards the Performance of Local Governments. This result is in line with the studies conducted by Andani & Respati (2019); Aswar (2019); Dewata et al (2018); as well as Sutopo and Siddi (2018), which used samples from Districts/Cities in the whole of Indonesia in the period of 2010-2018. The result of the study showed that Audit Opinion has a significant and positive effect.…”
Section: Modelsupporting
confidence: 90%
“…Audit Opinion: According to Andani and Respati (2019), the obtainment of an unqualified opinion enables a local government to be assessed well and its financial reports can be trusted. The fulfillment of financial reports follows standards, disclosures, obedience towards regulations, and effectiveness of the internal control system.…”
Section: Local Wealth Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…As users of the accrual-based Government Accounting Standards, local governments will follow the regulations set by the central government. This accrual-based Government Accounting Standard produces public sector information that has been adjusted to GAAP so that public sector financial practices are more orderly and more accurate [8,[11][12][13][14][15][16].…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…In terms of financial performance, it is predicted that greater size will improve the region's financial performance and vice versa. Masdiantini and Erawati (2016), Andani et al (2019), andIslami et al (2020) investigated the impact of local government size on the financial performance of local governments.…”
Section: Government Size and Financial Performancementioning
confidence: 99%